Improving Representation of Human Well-Being and Cultural Importance in Conceptualizing the West Hawai‘i Ecosystem - Leong, Kirsten M.; Wongbusarakum, Supin; Ingram, Rebecca J.; Mawyer, Alexander; Poe, Melissa R. (Frontiers in Marine Science, 2019)
Ecosystem-based management approaches are increasingly used to address the critical linkages between human and biophysical systems. Yet, many of the recently developed social-ecological systems (SES) frameworks neither represent the social and ecological aspects of the system in equal breadth or depth, nor do they adequately operationalize social dimensions. The National Oceanic and Atmospheric Administration’s West Hawaiʻi Integrated Ecosystem Assessment, a program grounded in ecosystem-based management, recognizes the importance of place-based human dimensions in coastal and marine resource management that speak to a fuller range of social dimensions of ecosystem-based management. Previous work with stakeholders in West Hawaiʻi revealed significant SES dynamics and highlighted both the importance and lack of understanding of the links between ecosystem services and human well-being, particularly services that enhance and maintain cultural connections to a place. While cultural ecosystem services and human well-being are often recognized as important elements of SES, there have been substantial barriers to fully representing them, likely due to perceived difficulties of measuring intangible benefits and values, many which are socially constructed and subjective. This study examined SES frameworks related to cultural ecosystem services and human well-being to advance the representation and operationalization of important social aspects of SES in broad conceptual frameworks. We describe key insights and questions focused on: (1) points of inclusion for social elements in SES models, (2) culturally relevant domains of human well-being and related indicators, (3) the importance of place and its interaction with scale, and finally (4) the tension between a gestalt vs. discrete approach to modeling, assessing, and sustainably managing social-ecological systems.